New Flat Surfaces in S3 - V. Corro, Armando M. (2021)
In this paper, we consider a method of constructing flat surfaces based on Ribaucour transformations in S3. By applying the theory to the flat torus, we obtain a family of complete flat surfaces in S3 which is determined by several parameters. We provide explicit examples.